Leveraging journal citation-based metrics for enhanced university rankings methodology - Ghaddar, Ali; Thoumi, Sergio; Saab, Samer S. (Frontiers in Research Metrics and Analytics, 2024)
This paper proposes a novel framework for evaluating research performance in university rankings, utilizing journal citation-based metrics and scholarly output instead of traditional article citation metrics. Through correlation analysis, we compare the proposed metrics with article citation metrics used by prominent ranking systems (THE and QS) and demonstrate significantly higher correlations with established rankings (QS, THE, and ARWU). The proposed metrics exhibit robustness over time and offer a fairer evaluation by emphasizing objective performance and mitigating citation biases. This framework provides institutions with a more accurate benchmarking tool to inform strategic decisions and resource allocation. While acknowledging potential limitations in data availability and the challenge of achieving global consensus, this study contributes to the ongoing discourse on university rankings by advocating for a more equitable and robust evaluation system by balancing diverse metrics and offering more standardized measures.